Binyat ar-Ramz al-Lugawiyyah fī at-Tafsīr aṣ-Ṣūfī - Muhammad Farid Abdullah; Ahmad Agus Suaidi (IAIN Salatiga, 2022)
This research aimed to demonstrate the distinctive and comprehensive scholarship of the Sufi knowledge structure. The descriptive method and comparative analysis were used in this literature study. Meanwhile, the data were obtained through a review of the literature, which included books, journals, and academic writings with both primary and secondary references. Through in-depth readings, the researchers found that Sufi thought tends to be symbolic and unconventional. They exist in a sort of semantic intensity that is organized by open spiritual experience, which by nature is in alignment with various symbolic objects and their various manifestations by a strong spiritual sense, equipped with imagination and intuition that emanates from the depths of their being. There are numerous sign systems used in the Sufi language that, in terms of functionality, go beyond those used in conventional language. The study's findings suggest that symbols have the following qualities in the intuitive dimension: First, mystical knowledge produces symbols (Gnosticism). The foundation of sufi symbols is the integration of mental, emotional, and spiritual intelligence. Second, the symbolism that Sufis understand is very extensive. The Sufi is endowed with the power to reveal different secrets and inner truths when he reaches the state of mukafah and muhadah. He is capable of understanding sign language's symbolic expressions. Third, symbols offer a wide range of possible interpretations. Symbolism is based on an approach to interpretation that, by accurately reproducing meaning, broadens thought. This talent shows how the Sufi's spiritual level evolved from the sensory level to the level of infinite totality.